Expert systems principles and programming - Giarratano, Joseph C.; Riley, Gary, 1962- (Boston : Course Technology, 2005)
The new edition of this market-leading text builds upon the blend of expert systems theory and application established in earlier editions.
Accompanied by a CD-ROM shelved at the Reserve Desk.
Includes bibliographical references and index.
All Ages.
System requirements for accompanying CD-ROM: Mac/Windows/Unix.
Keywords: Expert systems (Computer science).